Dealing with Diversity - Levin, Benjamin; Riffel, J. Anthony (Education Policy Analysis Archives, 1994)
Increasing diversity in the population is a major issue for educators in North America, presenting political as well as educational challenges. This paper examines Canadian educational policy responses to four kinds of diversity - bilingualism (French/English), multiculturalism, the situation of aboriginal peoples, and the problem of poverty. A description of each issue leads to some speculations or propositions on the nature of diversity and appropriate educational responses to it.